2011
DOI: 10.1007/s00284-011-9874-8
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Bacterial Community in the Food Waste-Reducing Larvae of Hermetia illucens

Abstract: As it is known that food waste can be reduced by the larvae of Hermetia illucens (Black soldier fly, BSF), the scientific and commercial value of BSF larvae has increased recently. We hypothesised that the ability of catabolic degradation by BSF larvae might be due to intestinal microorganisms. Herein, we analysed the bacterial communities in the gut of BSF larvae by pyrosequencing of extracting intestinal metagenomic DNA from larvae that had been fed three different diets. The 16S rRNA sequencing results prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
141
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(160 citation statements)
references
References 40 publications
12
141
1
6
Order By: Relevance
“…Jeon et al (2011) reported that a signifi cant factor is amount and composition of bacteria in the digestive tract of the larvae HI. Yu et al (2011) have even proven impact on growth and development of larvae HI a er inoculating poultry manure with bacteria from HI larvae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jeon et al (2011) reported that a signifi cant factor is amount and composition of bacteria in the digestive tract of the larvae HI. Yu et al (2011) have even proven impact on growth and development of larvae HI a er inoculating poultry manure with bacteria from HI larvae.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that Hermetia illucens larvae are used for reducing weight of food waste (Zheng et al, 2012;Jeon et al, 2011) and for reducing weight of manure Yu et al, 2011;Myers et al, 2008;Newton et al, 2005). For very favourable results, the usage of HI for the treatment of biowaste is discussed not only in states, where the incidence of HI is natural (Diener et al, 2009) but also in states where you will need to use controlled breeding (Holmes et al, 2012), as in the case of Czech Republic.…”
mentioning
confidence: 99%
“…아메리카동애등에의 장내 미생물을 메타게놈 방식으로 분석한 결과 6개 문의 세균류가 검출되었다 (Jeon et al, 2011). 일반적 으로 이러한 장내 미생물은 소화, 발육 및 면역에 중요한 역할 을 담당할 뿐만 아니라 병원 미생물의 정착을 억제하는 데 요구 된다 (Qin et al, 2010;Roh et al, 2008;Yu et al, 2008).…”
unclassified
“…일반적 으로 이러한 장내 미생물은 소화, 발육 및 면역에 중요한 역할 을 담당할 뿐만 아니라 병원 미생물의 정착을 억제하는 데 요구 된다 (Qin et al, 2010;Roh et al, 2008;Yu et al, 2008). (Jeon et al, 2011;Zheng et al, 2013).…”
unclassified
“…BSF larvae are known to dramatically reduce food waste and to convert the nutrients from food waste and manure into insect larval biomass (Kim et al, 2008;Diener et al, 2009). Thus, the BSF larva itself is a potential high protein and high energy feed as well as a resource for isolation of novel species of bacteria, archaea, yeasts and protists from insect guts of adults and larvae (Breznak, 1982;Brauman et al, 2001;Hongoh et al, 2003;Schmitt-Wagner et al, 2003;Ohkuma, 2008;Kudo, 2009;Jeon et al, 2011;Kim et al, 2013). …”
mentioning
confidence: 99%